Energy efficiency joint optimization algorithm for low-precision ADC massive MIMO systems - Haiyan CAO; Wenjuan HU; Yingjuan ZHI; Fangmin XU; Xin FANG (Dianxin kexue)
An uplink energy efficiency optimization algorithm based on alternating optimization algorithm was proposed for large-scale multiple-input multiple-output (MIMO) systems with low-precision analog to digital converters (ADC).That is,based on the maximum ratio combining (MRC) reception,an optimization model aiming at maximizing energy efficiency was established,and then the original fractional form optimization problem was converted into an equivalent subtractive form according to the nature of the fractional programming.In the case where the number of quantization bits was constant,the iterative optimization of the transmission power and the pilot length were performed.Simulation results show that the proposed algorithm has better spectral efficiency and energy efficiency.